2021
DOI: 10.52380/ijpes.2021.8.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Item Response Theory based Psychometric Investigation of SWLS for University Students

Abstract: Life satisfaction is an important factor for mental health and has many positive effects on people. Considering its importance, different measurement tools were developed over the last 5 years. Among these tools, the Satisfaction with Life Scale (SWLS) is the most prominent and adapted to diverse populations, including university students. On the other hand, all these studies were conducted using the classical testing approach, while item response theory was rarely preferred. Regarding this gap, this study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…The CQS prepared by Ang et al (2007) point scale appears to be less confusing and to increase response rate (Babakus & Mangold, 1992;Devlin et al, 1993). Some similar studies (Avcu, 2021) used similar Likert scales and suggested that the seven response categories were too high and should be reduced to five to decrease disturbance for participants and make it easier for them to distinguish between adjacent categories.…”
Section: Methodsmentioning
confidence: 99%
“…The CQS prepared by Ang et al (2007) point scale appears to be less confusing and to increase response rate (Babakus & Mangold, 1992;Devlin et al, 1993). Some similar studies (Avcu, 2021) used similar Likert scales and suggested that the seven response categories were too high and should be reduced to five to decrease disturbance for participants and make it easier for them to distinguish between adjacent categories.…”
Section: Methodsmentioning
confidence: 99%
“…Velmi vhodnou metodou pro hodnocení kvality a vývoj škál je pak teo rie odpovědi na položku (Item Response Theory, "IRT"), která však v případě SWLS nebyla dosud příliš aplikována (Avcu, 2021;Nima et al, 2020;Oishi, 2006;Vittersø et al, 2005). Jde o poměrně moderní metodologický přístup založený na matematickém modelování vztahu latentní proměnné a měřitelné odpovědi na konkrétní položku v rámci celého testu či škály, čímž se právě primárně odlišuje od CTT, která pracuje s celým testem/škálou.…”
Section: Konfirmační Faktorová Analýza (Cfa) a Teorie Odpovědi Na Pol...unclassified
“…Higher score implies higher life satisfaction. People with higher sores in SWLS are more compatible with and productive in society (Avcu, 2021) who found that SWLS items did not show gender-bias i.e. SWLS items functioned similarly for men and women.…”
Section: If I Could Live My Life Over I Would Change Almost Nothingmentioning
confidence: 99%
“…and how frequently an action is to take place for regarding it as most ways. Participants may find it difficult to distinguish between adjacent category levels (Avcu, 2021).…”
Section: Literature Surveymentioning
confidence: 99%